Official Development Assistance; A Succor To Manufacturing That Enhance Economic Growth In SADC - Gomolemo Gashiten (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
The aim of this study was to establish ODA as an aid to manufacturing that leads to economic growth using data from Southern Africa Development Community (SADC) countries. The study adopted manufacturing as a percentage of GDP as a mediator between ODA and economic growth. The United Nations report (2020) observed that close to half of the population in the region are living below the poverty datum line. This is why the researcher saw it fitting to conduct a research on how ODA can better result into economic growth. The theory that was utilized in the research is the Absorptive capacity model which helped in developing a theoretical framework that links manufacturing as a mediating variable between ODA and economic growth. Absorptive capacity formed a very important aspect in this research and it is measured by manufacturing. The Random Effects Model was also used in data analysis which revealed that ODA has positive impact on economic growth.